Reduced graphene oxide supported Ni@Au@Pd core@bishell nanoparticles as highly active electrocatalysts for ethanol oxidation reactions and alkaline direct bioethanol fuel cells applications. (1st May 2018) - Wang, Fang; Qiao, Jinshuo; Wang, Jun; Wu, Haitao; Yue, Xinyang; Wang, Zhenhua; Sun, Wang; Sun, Kening
Abstract: A novel Pd-based ternary core@bishell (Ni@Au@Pd) nanocatalysts supported on reduced graphene oxide were prepared via a facile method and exhibited high catalytic activity in half-cell reactions and fuel cell applications towards ethanol oxidation. The nature of this core@bishell nanocatalysts was clearly proved by the morphology characterization. Meanwhile, we found that the enhanced electrocatalytic property was attributed to the use of graphene, the optimized electronic properties of Pd shell tuned by the sub-layer Au metal atom as well as the assistant catalysis of Au sub-shell. Notably, with this highly active nanocatalysts as anode, the anion exchange membrane based direct bioethanol fuel cell achieved a single cell performance as high as 185.78 mW cm −2 with a low Pd loading of 0.5 mg Pd cm −2 under 80 °C and ambient pressure. It outperforms that of commercial Pd/C or Pt/C with the comparative conditions and is comparable to pure methanol or ethanol, as well as high performance direct biomass-derived fuel cell.